Hegemonic transition: global economic and security orders in the age of Trump - Böller, Florian; Werner, Welf (Springer International Publishing, 2021)
Introduction: Hegemony, Contestation and Transition -- Externalizing the Costs of Leadership: The Impact of Changing State-Societal Relations on US Hegemony -- Broken Social Contract: The Domestic Roots of US Hegemonic Decline in the World -- Exit from US Leadership: Global Trade Policy and Trump’s “America First” Doctrine -- Decay of US Economic Hegemony? Intellectual Property Rights, Dollar Centrality, and US Geo-economic Power -- Leading by Example or Extortion? US Leadership Role Transition and the Non-Proliferation Regime -- The End of NATO as We Know It: Reconfiguring Transatlantic Security Relations -- Institutional Contestation: The Trump Administration and International Organizations -- Spoiler State: Russia’s Status Seeking and Hegemonic Ambitions -- Contested Cyberspace: China’s Increasing Role and Power in Technology Governance -- Between a Rock and a Hard Place: India’s Response to the Hegemonic Decline of the West -- Dual Hegemony: Brazil between the United States and China -- Fast-track towards a Hegemonic Transition: Corona and the Decline of US Hegemony -- Conclusion.
Keywords: Erde